100W triac dimmable LED driver with PFC - Ocampo, Rolf Emmanuel D. (2011)
This undergraduate research project tackles the implementation and use of a single stage flyback converter. The latest advancements in integrated circuits will be used to provide a simple solution in power factor correction requirements. Standard tests will be applied to ensure the effectiveness and safety of the project. By the end of the semester, the project should be able to run at 220Vrms, an output voltage of 48V for the flyback converter with a maximum output current of 2.1A and 44V output for the buck converter with a 700mA output current each. The flyback controller did not achieve any form of power factor correction as opposed to what was initially expected. A traditional flyback converter using the UC3843 was designed to drive 33W or one of the three buck converters directly from the line. Although it was able to drive 1/3 of the load, it failed to dim the LED as an input capacitor was used to the UC3843 to start-up. The buck controller gives a constant current control for the LEDs as well as an easy way of dimming it using TTL logic PWM input. Each of the three buck converters was able to drive the expected load of 11 3W HB LEDs. Using the zero-crossing detector gave the cleanest signal that the microcontroller can interpret. The use of the microcontroller also prove to be the fastest way of generating a PWM signal given an analog signal.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Electric current converters; Light emitting diodes